2014
DOI: 10.3354/dao02716
|View full text |Cite
|
Sign up to set email alerts
|

White bass Morone chrysops is less susceptible than its hybrid to experimental infection with Flavobacterium columnare

Abstract: Hybrid striped bass (HSB) and white bass (WB) were evaluated for their susceptibility to Flavobacterium columnare, the causative agent of columnaris disease, in 3 fundamental studies. In the first experiment, we determined whether columnaris disease could be developed by experimental challenge in HSB. This challenge consisted of 3 levels of F. columnare (10, 30, and 60 ml volumes) determined to be 2.25 × 10 7 , 6.75 × 10 7 , and 1.35 × 10 8 CFU ml −1 , respectively. Each treatment group exhibited significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 28 publications
2
12
0
Order By: Relevance
“…Flavobacterium columnare isolate LSU‐066‐04 was used for the current study because it was originally isolated from largemouth bass ( Micropterus salmoides ) at the Louisiana Aquatic Diagnostic Lab and the previous work done in moronids model (Beck et al., 2015; Fuller et al., 2014; Lange et al., 2017). The F. columnare isolate was retrieved from frozen glycerol stocks and streaked onto F. columnare growth medium (FCGM) (Darwish et al., 2008; Farmer, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavobacterium columnare isolate LSU‐066‐04 was used for the current study because it was originally isolated from largemouth bass ( Micropterus salmoides ) at the Louisiana Aquatic Diagnostic Lab and the previous work done in moronids model (Beck et al., 2015; Fuller et al., 2014; Lange et al., 2017). The F. columnare isolate was retrieved from frozen glycerol stocks and streaked onto F. columnare growth medium (FCGM) (Darwish et al., 2008; Farmer, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Disease susceptibility has been shown to vary depending on fish species and pathogen (Arias et al., 2012; Griffin et al., 2010; Reichley et al., 2018; Xu et al., 2014). However, previous research showed that WB exhibit superior survival to disease challenges with F. columnare , as compared to hybrid striped bass (Fuller et al., 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies found that the LSU isolate was highly virulent in white bass Morone chrysops , hybrid striped bass Morone chrysops x Morone saxatilis and channel catfish (Beck et al . ; Fuller, Farmer & Beck ). Building upon these previous reports, the present study is the first head‐to‐head comparison of these two isolates in a single host species.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and genomic tools are needed to support the ongoing domestication and selective breeding efforts of the USDA‐ARS Stuttgart National Aquaculture Research Center (SNARC; Stuttgart, AR), aimed at providing the industry with a superior and sustainable, cultured broodstock source (Fuller & McEntire ; Fuller et al . , ; Li et al . ).…”
Section: Geographic Coordinates Number Of Individuals (N) and Genetimentioning
confidence: 99%